2017
DOI: 10.1111/emip.12173
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Freshman Grade‐Point Average from Test Scores: Effects of Variation Within and Between High Schools

Abstract: Most studies predicting college performance from high‐school grade point average (HSGPA) and college admissions test scores use single‐level regression models that conflate relationships within and between high schools. Because grading standards vary among high schools, these relationships are likely to differ within and between schools. We used two‐level regression models to predict freshman grade point average from HSGPA and scores on both college admissions and state tests. When HSGPA and scores are conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…For judging college readiness, school-average ACT scores would provide a stronger prediction than students’ individual scores. This is consistent with the findings and recommendations in Koretz and Langi (2018) and Bowen et al (2009). The same pattern is observed with school-average poverty levels (in models that do not control for average ACT scores), which echoes Rothstein’s (2004) findings.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For judging college readiness, school-average ACT scores would provide a stronger prediction than students’ individual scores. This is consistent with the findings and recommendations in Koretz and Langi (2018) and Bowen et al (2009). The same pattern is observed with school-average poverty levels (in models that do not control for average ACT scores), which echoes Rothstein’s (2004) findings.…”
Section: Discussionsupporting
confidence: 93%
“…The similarity in results that are available from studies of schools in other places provides some indication of their generalizability. Studies that used data from samples that include 21 prestigious flagship universities from across the country and all public universities in four states (Bowen et al, 2009; Koretz & Langi, 2018; Rothstein, 2004) all showed that HSGPAs are strongly related to either college graduation or to college freshman GPA and that students’ individual ACT or SAT scores add only modestly to the prediction beyond HSGPA, if at all, in models that include high school fixed effects and compare similar colleges. The graduation rates presented by Bowen et al (2009) for specific HSGPAs are also similar to the graduation rates found here and shown in Figure 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the comparison made in this study between the performance of students coming from high school and those who passed the preparatory year shows that direct admission from high school to colleges is less convincing in assessing students' readiness to enroll in colleges. These results have been confirmed by Koretz and Langi (2018), who found that high school grades are not sufficient to predict students' performance at university because grading standards vary significantly.…”
Section: Discussionmentioning
confidence: 69%
“…Using a component analysis approach to stem a decision tree, the study found that the data need to be applied as a whole for a successful prediction of grades, particularly to predict failure. Koretz and Langi (2018) found that grading standards in high schools vary significantly; therefore, they are not sufficient to predict performance at university. As a result, the researchers used regression models to predict the college performance of freshmen based on scores in high school and admission and state tests.…”
Section: Literature Reviewmentioning
confidence: 99%